NanoSIMS Analysis of Rare Earth Elements in Silicate Glass and Zircon: Implications for Partition Coefficients - Shi, Lanlan; Sano, Yuji; Takahata, Naoto; Koike, Mizuho; Morita, Takuya; Koyama, Yuta; Kagoshima, Takanori; Li, Yuan; Xu, Sheng; Liu, Congqiang (Frontiers in Chemistry, 2022)
We have developed a method to analyze all rare earth elements in silicate glasses and zircon minerals using a high lateral resolution secondary ion mass spectrometer (NanoSIMS).　A 2nA O- primary beam was used to sputter a 7-8 m diameter crater on the sample surface and secondary positive ions were extracted for mass analysis using an accelerating voltage of 8 kV. A high mass resolving power of 9,400 at 10% peak height was attained to separate heavy REE from oxide of light REE. A multi-collector system combined with peak-jumping by magnetic field was adjusted to detect REEs and silicon-30 for calibration. Based on results of NIST SRM610 glass, sensitivities of REEs vary from 3 cps/ppm/nA of Lu to 13 cps/ppm/nA of Eu. Reproducibility of REE/Si ratios is better than 18% at 2. Secondary ion yields of REEs show positive relationships with their ionization potential of second valence. REEs of AS3, QGNG and Torihama zircons were measured and calibrated against those of 91500 standard zircon. SIYs of REEs of zircon are identical to those of the glass standard. AS3 and QGNG data are generally consistent with those of previous work. Torihama REE data combined with the whole rock data provide partition coefficients of REEs between silicate melt and zircon. The relationship between these coefficients and ionic radius is explained by an elastic moduli model.